A case of nosebleeds in Osler-Weber-Rend syndrome - Romanenko, Roman; Laziuk, Snizhana; Tarasenko, Maksym; Dovgych , Serhiy (The Ukrainian Scientific Medical Youth Journal, 2025)
hereditary hemorrhagic telangiectasia (HHT), or Osler-Weber-Rend syndrome, is a genetic autosomal dominant disease. The cause of HHT is mutations in genes involved in angiogenesis, primarily ENG, ACVRL1 and SMAD4, which leads to vascular dysplasia and, as a result, telangiectasias, recurrent bleeding and arteriovenous malformations. The prevalence of HHT is 1 in 5,000-10,000 people. HHT can occur at any age, and symptoms can vary greatly in different people due to the nature of genetic mutations, which complicates diagnosis. To focus the attention of the medical community on HHT and to promote the development of effective approaches to its diagnosis and therapy of HHT, particularly in the context of epistaxis. The study analyzed the experience of treating a patient with hereditary hemorrhagic telangiectasia (HHT), who presented with complaints of epistaxis. The patient was clinically examined and treated according to the Ukrainian Unified Clinical Protocol for the Treatment of Epistaxis. The following treatments were used: hemostatic tampons, to temporarily stop nasal bleeding due to their ability to quickly absorb blood and create mechanical pressure on the bleeding site; fibrin thread swabs, which were used to improve hemostasis and stimulate the natural blood clotting process; diathermy, as local cauterization of bleeding areas of the nasal mucosa to reduce bleeding; hormonal therapy with dexamethasone, which was used to reduce inflammation and reduce the frequency of bleeding; antifibrinolytic therapy with tranexamic acid, to inhibit fibrinolysis and reduce the risk of recurrent bleeding; and anti-inflammatory therapy with diclofenac, which was prescribed to reduce pain, swelling, and inflammation in patients with complications of nosebleeds. A 76-year-old woman was brought to the otolaryngology department with recurrent epistaxis. The patient was diagnosed with SGT according to the Curacao diagnostic criteria (Clinical guideline of the French Association of Otorhinolaryngologists from 2016) based on clinical data, medical history, and family history. Treatment was carried out using non-surgical methods of treatment and consultation with such doctors as: geneticist, rheumatologist, gastroenterologist. After the therapy, the woman was discharged 2 weeks after admission in a satisfactory condition with recommendations for preventing bleeding. This case emphasizes the importance of early diagnosis of SHT, an individual approach to treatment and the need to expand the possibilities of SHT treatment in Ukraine.